Artefact co-construction in virtual exchange: 'Youth Entrepreneurship for Society'. Issue 7 (3rd September 2022) - Sevilla-Pavón, Ana; Nicolaou, Anna
Abstract: The aim of this research study around the co-construction and sharing of authentic and meaningful artefacts within the 'Youth Entrepreneurship for Society' virtual exchange was to find out how the implementation of artefact-based telecollaborative tasks fosters 21st competences and social entrepreneurship in English for Specific Purposes settings. The project tasks were informed by constructionism and supported virtual collaboration an effort to promote social justice. They revolved around social entrepreneurship in English for Specific Purposes contexts, aiming to connect the classroom with the outside world through the involvement of local organisations, while fostering students' twenty-first century competences: intercultural, linguistic, digital and teamwork as well as social entrepreneurial mindset. The two research questions which guided the study were: (1) How does the implementation of artefact-based tasks in English for Specific Purposes contexts contribute to students' perceived development of twenty-first century competences? (2) In what ways can the implementation of artefact-based telecollaborative tasks foster social entrepreneurship in English for Specific Purposes contexts? The results of the study conducted with 42 participants indicate that the virtual exchange was perceived as having positively contributed to connecting the classroom with the outside world through the involvement of mentor civil organisations, while fostering students' twenty-first century competences.